2017
DOI: 10.1016/j.rboe.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

PRWE application in distal radius fracture: comparison and correlation with established outcomes

Abstract: ObjectiveThe study aimed to evaluate the correlation between the PRWE score with other measurements that are already widely used.MethodsThis was a prospective, cross-sectional, single-center study. Sixty-eight consecutive patients underwent surgical treatment for distal radius fractures (internal fixation by locked volar plate or transarticular external fixation). They were evaluated independently by PRWE, DASH, VAS range of motion, strength, and radiographic criteria, in one year of follow up. The Mann–Whitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…20 The PRWE represents a validated outcome score specifically evaluating the wrist and distal radius fractures. 38,39 The maximal functional improvement and most change in PRWE score after sustaining a distal radius fracture Table 7 Radiographic parameters were measured at the time of each clinical follow-up Note: There were no statistical differences noted between the BFR and control group for any time point as well as in the BFR group before initiation of BFR and at terminal follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…20 The PRWE represents a validated outcome score specifically evaluating the wrist and distal radius fractures. 38,39 The maximal functional improvement and most change in PRWE score after sustaining a distal radius fracture Table 7 Radiographic parameters were measured at the time of each clinical follow-up Note: There were no statistical differences noted between the BFR and control group for any time point as well as in the BFR group before initiation of BFR and at terminal follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The DASH is a validated tool to measure outcomes of upper limb injuries, including DRF . Although there are other techniques of outcome measures following DRF management such as Patient Reported Wrist Evaluation (PRWE), it has been reported that there is a strong correlation between DASH and PRWE scores . Some authors used pain scores to assess the outcome of DRF .…”
Section: Methodsmentioning
confidence: 99%
“…4,[12][13][14][15][16] Although there are other techniques of outcome measures following DRF management such as Patient Reported Wrist Evaluation (PRWE), it has been reported that there is a strong correlation between DASH and PRWE scores. 16 Some authors used pain scores to assess the outcome of DRF. 4 However, DASH has designated questions (question no.…”
Section: Dash Questionnairementioning
confidence: 99%
“…[39][40][41][42][43] The PRWE score is a validated method to determine functional disability following DRFs. 24,44,45 Regardless of whether a patient is treated by operative or nonoperative means following a DRF, most improvements in strength, ROM, and function are typically made within the first 3 to 6 months. 11 Similarly, in a meta-analysis of DRFs stabilized with volar plate fixation, significant improvements in PRWE scores were seen within the first 6 months before scores plateaued.…”
Section: Discussionmentioning
confidence: 99%